THE EFFECT OF APPLYING OUTDOOR ACTIVITY ON THE STUDENT’S WRITING ABILITY IN DESCRIPTIVE TEXT AT SMP IT SUARA DA’I MUDA LANGKAT - Zahrah, Abirah Tuz (Faculty of Tarbiyah nad Teacher Training, 2021)
The study was intended to understand the effect of the Outdoor Activity approach on the writing capacity of the students observed and evaluated by seven-grade students at SMP IT Suara Da'I Muda Langkat. Experimental study design was the approach used. The population in this study was seven grade of the Students of SMP IT SuaraDa'I Muda Langkat. The researcher took all of the population of the seven grades, there are two classes and divided them as experimental and control class while taking the sample of this study. In the experiment, there were 25 students and 25 students in control class. The researcher taught in the experimental class using the Outdoor Activity technique and thye control class taught using the Lecturing approach. The investigator used pre-test, treatment, and post-test. The experimental class increased from 56,40 to 75,80 by 19,4 points, while the control class increased from 49,60 to 65,60 by 16 points. The researchers found that the value of Sig was determined by using SPSS V22 in the post-test of the experiment and control class.It was 0,000 in the T-Test (2tailed). It was lower than 0,05 (0,000<,0.05), so there was a substantial distinction between the class of the experiment and the class of the monitor. In other words, by using the Outdoor Activity approach, the achievement of the students in writing is more successful than the method of lecturing.